2015
DOI: 10.1016/j.forpol.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Teak–cattle production tradeoffs for Panama Canal Watershed small scale producers

Abstract: Reforestation and forest conservation are important issues in the Panama Canal Watershed (PCW). Uncertainty remains about relative net benefits of profit-maximizing timber rotations compared to the net present value of incumbent land uses such as cattle ranching. The scientific and popular literatures have displayed enthusiasm for teak (Tectona grandis) and native species plantations. We estimate a realistic yield model for teak, an exotic tree species, based on growth data from actual small scale landholders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Tewari et al [20] obtained similar results for calculating volumes of teak grown in India. Consideration of heteroscedastic conditions provided superior results to those obtained for teak in earlier studies [8,44,45,49,50]. These authors used polynomial methods (classic minimum squares methods) and non-linear regression techniques (Marquard's method) to establish the volume of teak and selected the best fit volume models (Schumacher-Hall) in accordance with statistics such as the coefficient of determination (R 2 ) and the statistical significance of the estimated parameters, without considering heteroscedastic conditions.…”
Section: Volume Equations For Teak In Spsmentioning
confidence: 68%
See 1 more Smart Citation
“…Tewari et al [20] obtained similar results for calculating volumes of teak grown in India. Consideration of heteroscedastic conditions provided superior results to those obtained for teak in earlier studies [8,44,45,49,50]. These authors used polynomial methods (classic minimum squares methods) and non-linear regression techniques (Marquard's method) to establish the volume of teak and selected the best fit volume models (Schumacher-Hall) in accordance with statistics such as the coefficient of determination (R 2 ) and the statistical significance of the estimated parameters, without considering heteroscedastic conditions.…”
Section: Volume Equations For Teak In Spsmentioning
confidence: 68%
“…Griess and Knoke [51] calculated a yield of 250 m 3 ha −1 at 30 years. Quintero et al [52] reported volume yields between 193 -337 m 3 ha −1 for teak in Colombia at 60 years, and Stefanski et al [50] presented yields of 67.5-88.6 m 3 ha −1 at 30 years. The MAI for the best SI in the study area was 15.3 m 3 ha −1 year −1 at an age of 15 years for the SPS and a density of 160 trees ha −1 .…”
Section: Teak Production In Spsmentioning
confidence: 99%
“…In Panama, Tectona plantations represent 76% of the timber trees planted between 1992 and 2002 [5]. However, Tectona does not grow particularly well on the acidic clay soils typical of many areas of Panama, including around the Panama Canal Watershed [6]. This is of concern because the failure of commercial reforestation projects not only reduces the return on investments by landowners but can also have negative consequences for overall ecosystem function.…”
Section: Introductionmentioning
confidence: 99%
“…Integrated systems is widely used by smallholder (Herrero et al, 2014;Riedel et al, 2014) by utilizing the potential of surrounding natural resources as the carrying capacity in the development of beef cattle enterprise (Vanlauwe et al, 2014). For example, forests and crops provide linkages interaction with cattle (Peyraud et al, 2014;Stefanski et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The key to success in the development of beef cattle enterprise is the competence of farmers in utilizing natural resources optimally (Dossa et al, 2015). For example, the utilization of natural resources as the carrying capacity of livestock provides feed for livestock thus forming a pattern of integration between cattle enterprise with agriculture and forests (Peyraud et al, 2014;Stefanski et al, 2015). Pattern of integration is expected to improve the cattle enterprise that operated.…”
Section: Introductionmentioning
confidence: 99%